Exploring the Effects of Using Authentic Materials to Foster the Comprehension of Writing Skills among EFL Students at a Public School (2022)
ABSTRACT: This article reports on a case study carried out in a public school located in Medellín, Colombia. Its main purpose was to explore the effects of using authentic materials to foster the comprehension of writing skills among EFL students in a fifth-grade classroom. Datawere collected through memos, two work samples, and a reflection task. The findings suggested that fables are adequate resources to foster the comprehension of writing skills, specifically sentence structure, and punctuation marks, as long as students are provided with proper scaffolding activities. Furthermore, the use of fables equally promoted in-classparticipation, vocabulary acquisition, and a reflective attitude toward values, characters, and situations depicted in the stories.